(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the efficacy of basic safety training for BSHM students in Compass Silang, Cavite, in terms of preventing loss of life, training individuals to react correctly, aiding treatment, increasing chances of survival, and the challenges they encountered during the basic safety training. Basic safety training has a huge contribution to our daily lives, and it can be applied anywhere to save the lives of many people. Training is really important to those people who are pursuing a course that is related to their career because it can enhance their skills and they can gain more knowledge from it. This study shows that the basic safety training in COMPASS Silang, Cavite, has been achieved in terms of preventing loss of life, training individuals correctly, aiding treatment, increase chances of survival. The things that need to be improved are in the lowest rank, which is basic safety training, which helps spot risky situations and avoid them, learn how to be calm in emergency situations, completeness and safety of supplies in first aid training are must, and know the techniques of water survival from the training. The researchers proposed guidelines on how to enhance basic safety training. This study recommends that basic safety training consider the feedback of the trainees, like their equipment, which should be hygienic because a lot of people use it, and also that we give the trainers time to familiarize themselves with the activities so they can apply them correctly and also consider the health of every person in the training so that assistance is always ready in case of emergency because that’s one of the purposes of basic safety training.